Effects of annealing on structure and deformation mechanism of isotactic polypropylene film with row‐nucleated lamellar structure. Issue 3 (3rd May 2013) - Ding, Zhitian; Bao, Ruiying; Zhao, Bo; Yan, Jing; Liu, Zhengying; Yang, Mingbo
ABSTRACT The effects of annealing on structure and deformation mechanism of isotactic polypropylene films with row‐nucleated lamellar structure were investigated. The microstructure developments of the lamellar structure and amorphous during annealing were detected by differential scanning calorimeter and Fourier transform infrared. As annealing went on, the "core–shell sandwich" lamellar structure was proposed to explain the unique tensile property and the microstructure changes of the annealed films. The recrystallized lamellar structure improved the ability of slipping resistance of original lamellar structure during stretching. Microporous membranes were produced through melt extrusion/annealing/uniaxial stretching way. The uniformities of micropore structure of microporous membranes were improved as the annealing time increased for the annealed films. As the "core–shell sandwich" structure developed during annealing, the shapes and diameters of micropore structure were getting more uniform. The annealing time for annealed films improved the water vapor transmission of the microporous membranes, indicating the increased interconnectivity of the pore structure. The pore dimensions of the microporous membranes measured by mercury porosimetry increased with the annealing time for annealed films. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1659–1666, 2013